2022
DOI: 10.13005/bpj/2402
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Ipomoea batatas L. Extract-Containing Capsule and Simvastatin Combination versus Simvastatin in Dyslipidemic Patients

Abstract: Purple sweet potato extract (PSPE) have been shown to exhibit antidyslipidemic effect, but the clinical effects of PSPE and statin combination has not been investigated. This study was aimed to reveal the effect of PSPE and statin combination on lipid profile, malondialdehyde (MDA) and superoxide dismutase (SOD) level in mild and moderate dyslipidemia cases. The study design was a limited clinical trial with a randomized pre and posttest control group design. Subjects were divided into simvastatin (control) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Subjects were determined by screening according to the inclusion criteria and divided into three groups purposively by considering the subject's ownership of a refrigerator for pudding storage and residence. The next step was blood collection and measurements of SOD and FBG before the intervention, followed by an intervention period of 28 days according to Basu et al (2021) and Subawa et al (2022) on human subjects that showed improvement in oxidative markers after 28 days of intervention. During the intervention, nutrition education was provided in week 1, while 2×24 hour food recall and physical activity data collection was performed in weeks 1-4.…”
Section: Samplingmentioning
confidence: 99%
“…Subjects were determined by screening according to the inclusion criteria and divided into three groups purposively by considering the subject's ownership of a refrigerator for pudding storage and residence. The next step was blood collection and measurements of SOD and FBG before the intervention, followed by an intervention period of 28 days according to Basu et al (2021) and Subawa et al (2022) on human subjects that showed improvement in oxidative markers after 28 days of intervention. During the intervention, nutrition education was provided in week 1, while 2×24 hour food recall and physical activity data collection was performed in weeks 1-4.…”
Section: Samplingmentioning
confidence: 99%